A method for preparing modified graphene
By performing sodium hydroxide and dilute acid treatment on graphene, combined with water cleaning and drying and crushing steps, the problem of insufficient graphene performance is solved, and the modified extreme pressure wear resistance, thermal conductivity and electrical conductivity are improved. .
Patent Information
- Application Number
- CN202211684250.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The existing graphene is relatively lacking in anti-wear, thermal conductivity and electrical conductivity, and a modification treatment method is needed to improve its performance.
The pH value of the ethanol solution is adjusted by sodium hydroxide, the graphene powder is modified, and then reacted in a dilute acid solution, washed and dried in water, and finally crushed. The modified graphene obtained has excellent extreme pressure resistance to wear. properties, thermal conductivity and electrical conductivity.
The modified graphene prepared by this method significantly improves its anti-wear, thermal and electrical conductivity, can maintain good performance under extreme pressure conditions, and enhance bonding strength by nano-copper oxide loading.
Smart Images

Figure CN116002675B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new material technology, and in particular, to a method for preparing modified graphene. Background Art
[0002] Graphene is a new material in which carbon atoms connected by sp2 hybridization are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. Graphene has excellent optical, electrical and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine and drug delivery. It is considered to be a revolutionary material in the future. Andre Geim and Konstantin Novoselov, physicists at the University of Manchester, successfully separated graphene from graphite by micromechanical exfoliation, and thus jointly won the 2010 Nobel Prize in Physics. The common methods for producing graphene powders are mechanical exfoliation, redox method, SiC epitaxial growth method, and the thin film production method is chemical vapor deposition method. People's research on the self-assembly of graphene is mainly focused on two-dimensional materials, such as graphene transparent conductive film, graphene thin film electrode, graphene polymer or nanocomposite material. Graphene is a new material with a single-layer sheet structure composed of carbon atoms, and is the thinnest nanomaterial known in the world.
[0003] The existing graphene has relatively poor anti-wear, thermal and electrical conductivity. Therefore, there is an urgent need for a method for modifying graphene to improve its anti-wear, thermal and electrical conductivity. Summary of the invention
[0004] The purpose of the present application is to provide a method for preparing modified graphene, wherein the modified graphene prepared by this method has the advantages of good wear resistance, thermal conductivity and electrical conductivity.
[0005] The present application solves the technical problem by adopting the following technical solution.
[0006] The present invention provides a method for preparing modified graphene, comprising the following steps:
[0007] Take graphene, add it to an ethanol solution, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution;
[0008] The mixed solution is stirred for reaction, and then filtered to obtain a filter residue;
[0009] Put the filter residue into a dilute acid solution and react until the pH value of the solution is 7, wash with water and drain, and then dry the filter residue;
[0010] The dried filter residue is crushed to obtain a modified graphene product.
[0011] In some embodiments of the present application, the particle size of the graphene is 50-150 nm.
[0012] In some embodiments of the present application, the ratio of the graphene to ethanol is 1 g:3 mL.
[0013] In some embodiments of the present application, the above ethanol concentration is 95%.
[0014] In some embodiments of the present application, the mixed solution is stirred for 3-5 hours and then allowed to stand for 2 hours.
[0015] In some embodiments of the present application, the above-mentioned dilute acid solution is specifically dilute sulfuric acid with a concentration of 7%.
[0016] In some embodiments of the present application, the above-mentioned washing of the filter residue with water is repeated 2-4 times.
[0017] In some embodiments of the present application, the above-mentioned drying condition is to dry the filter residue at a temperature of 55-65° C. for 4-6 hours.
[0018] In some embodiments of the present application, the above-mentioned crushing condition is to crush the filter residue at a rotation speed of 30,000 r / min for 40-90 s.
[0019] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0020] The present application uses sodium hydroxide to adjust the pH value of an ethanol solution, then adds graphene powder to modify it, adjusts the pH value with acid after the modification, then washes with water to remove residual sodium hydroxide, and finally dries and crushes it. The obtained modified graphene has excellent extreme pressure wear resistance, thermal conductivity and electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is the wear scar image of ball No. 1 in the four-ball experiment of the experimental example of this application;
[0023] Figure 2 This is the wear scar image of ball No. 2 in the four-ball experiment of the experimental example of this application;
[0024] Figure 3 This is the wear scar image of ball No. 3 in the four-ball test of the experimental example of this application. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.
[0027] The present invention provides a method for preparing modified graphene, comprising the following steps:
[0028] Take graphene, add it to an ethanol solution, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution;
[0029] The mixed solution is stirred for reaction, and then filtered to obtain a filter residue;
[0030] Put the filter residue into a dilute acid solution and react until the pH value of the solution is 7, wash with water and drain, and then dry the filter residue;
[0031] The dried filter residue is crushed to obtain a modified graphene product. The present application uses sodium hydroxide to adjust the pH value of an ethanol solution, then adds graphene powder to modify it, adjusts the pH value with acid after the modification, then washes with water to remove residual sodium hydroxide, and finally dries and crushes it. The obtained modified graphene has good extreme pressure wear resistance, thermal conductivity and electrical conductivity.
[0032] In some embodiments of the present application, the particle size of the graphene is 50-150 nm. The graphene with this particle size is processed to increase the contact area between the graphene and the modified solution, which can improve the reaction effect of the graphene.
[0033] In some embodiments of the present application, the ratio of the graphene to ethanol is 1 g: 3 mL. At this ratio, the graphene can be well wetted, making it easier to treat with sodium hydroxide.
[0034] In some embodiments of the present application, the above ethanol concentration is 95%.
[0035] In some embodiments of the present application, the mixed solution is stirred for 3-5 hours and then allowed to stand for 2 hours. After sufficient reaction, uniformly treated primary graphene can be obtained.
[0036] In some embodiments of the present application, the above-mentioned dilute acid solution is specifically dilute sulfuric acid with a concentration of 7%.
[0037] In some embodiments of the present application, the above-mentioned washing of the filter residue with water is repeated 2-4 times. Repeated washing can ensure that the sodium hydroxide in the filter residue is fully removed.
[0038] In some embodiments of the present application, the above-mentioned drying condition is to dry the filter residue at a temperature of 55-65° C. for 4-6 hours.
[0039] In some embodiments of the present application, the above-mentioned crushing condition is to crush the filter residue at a speed of 30000 r / min for 40-90 s. Under this condition, crushing can obtain a uniformly processed filter residue.
[0040] In some embodiments of the present application, after the filter residue is crushed, pine alcohol, nano copper oxide and the filter residue are evenly mixed in a weight ratio of 0.1:1:1, and treated at 450-490°C for 2-4h in an ammonia atmosphere to obtain a modified graphene product. By loading nano copper on graphene, the modified graphene can have good wear resistance, and the treatment at 450-490°C can enhance the bonding strength of the two.
[0041] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0042] Example 1
[0043] A method for preparing modified graphene comprises the following steps:
[0044] Take graphene with a particle size of 50 nm, add the graphene to a 95% ethanol solution at a ratio of 1 g:3 mL, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution;
[0045] The mixed solution was stirred for 3 h, allowed to stand for 2 h, and then filtered to obtain a filter residue;
[0046] Place the filter residue in a dilute acid solution (7% dilute sulfuric acid) and react until the pH value of the solution reaches 7. Wash with 500 mL of water and drain. Repeat this process twice. Dry the filter residue at 55°C for 4 hours.
[0047] The dried filter residue was crushed at a speed of 30000 r / min for 40 seconds, and then pineneol, nano copper oxide and the filter residue were evenly mixed in a weight ratio of 0.1:1:1, and treated at 450°C for 2 hours in an ammonia atmosphere to obtain a modified graphene product.
[0048] Example 2
[0049] A method for preparing modified graphene comprises the following steps:
[0050] Take graphene with a particle size of 80 nm, add the graphene to a 95% ethanol solution at a ratio of 1 g:3 mL, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution;
[0051] The mixed solution was stirred for 4 hours, allowed to stand for 2 hours, and then filtered to obtain a filter residue;
[0052] Place the filter residue in a dilute acid solution (7% dilute sulfuric acid) and react until the pH value of the solution reaches 7. Wash with 500 mL of water and drain. Repeat this process three times. Dry the filter residue at 58°C for 4.5 hours.
[0053] The dried filter residue was crushed at a speed of 30000 r / min for 50 seconds, and then pineneol, nano copper oxide and the filter residue were evenly mixed in a weight ratio of 0.1:1:1, and treated at 460° C. for 2-4 hours in an ammonia atmosphere to obtain a modified graphene product.
[0054] Example 3
[0055] A method for preparing modified graphene comprises the following steps:
[0056] Take graphene with a particle size of 100 nm, add the graphene to a 95% ethanol solution at a ratio of 1 g:3 mL, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution;
[0057] The mixed solution was stirred for 4 hours, allowed to stand for 2 hours, and then filtered to obtain a filter residue;
[0058] Place the filter residue in a dilute acid solution (7% dilute sulfuric acid) and react until the pH value of the solution reaches 7. Wash with 500 mL of water and drain. Repeat this process three times. Dry the filter residue at 60°C for 5 hours.
[0059] The dried filter residue was crushed at a speed of 30000 r / min for 60 seconds, and then pinene alcohol, nano copper oxide and the filter residue were evenly mixed in a weight ratio of 0.1:1:1, and treated at 470°C for 3 hours in an ammonia atmosphere to obtain a modified graphene product.
[0060] Example 4
[0061] A method for preparing modified graphene comprises the following steps:
[0062] Take graphene with a particle size of 120 nm, add the graphene to a 95% ethanol solution at a ratio of 1 g:3 mL, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution;
[0063] The mixed solution was stirred for 4 hours, allowed to stand for 2 hours, and then filtered to obtain a filter residue;
[0064] Place the filter residue in a dilute acid solution (7% dilute sulfuric acid) and react until the pH value of the solution reaches 7. Wash with 500 mL of water and drain. Repeat this process 4 times. Dry the filter residue at 63°C for 5 hours.
[0065] The dried filter residue was crushed at a speed of 30000 r / min for 70 seconds, and then pineneol, nano copper oxide and the filter residue were evenly mixed in a weight ratio of 0.1:1:1, and treated at 480°C for 3 hours in an ammonia atmosphere to obtain a modified graphene product.
[0066] Example 5
[0067] A method for preparing modified graphene comprises the following steps:
[0068] Take graphene with a particle size of 150 nm, add the graphene to a 95% ethanol solution at a ratio of 1 g:3 mL, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution;
[0069] The mixed solution was stirred for 5 h, allowed to stand for 2 h, and then filtered to obtain a filter residue;
[0070] Place the filter residue in a dilute acid solution (7% dilute sulfuric acid) and react until the pH value of the solution reaches 7. Wash with 500 mL of water and drain. Repeat this process 4 times. Dry the filter residue at 65°C for 6 hours.
[0071] The dried filter residue was crushed at a speed of 30000 r / min for 90 seconds, and then pineneol, nano copper oxide and the filter residue were evenly mixed in a weight ratio of 0.1:1:1, and treated at 490°C for 4 hours in an ammonia atmosphere to obtain a modified graphene product.
[0072] Example 6
[0073] A method for preparing modified graphene comprises the following steps:
[0074] Take graphene with a particle size of 100 nm, add the graphene to a 95% ethanol solution at a ratio of 1 g:3 mL, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution;
[0075] The mixed solution was stirred for 4 hours, allowed to stand for 2 hours, and then filtered to obtain a filter residue;
[0076] Place the filter residue in a dilute acid solution (7% dilute sulfuric acid) and react until the pH value of the solution reaches 7. Wash with 500 mL of water and drain. Repeat this process three times. Dry the filter residue at 60°C for 5 hours.
[0077] The dried filter residue was crushed at a rotation speed of 30000 r / min for 60 s to obtain a modified graphene product.
[0078] Experimental example
[0079] (I) According to SH / T0204-1992 "Determination of Anti-wear Performance of Grease (Four-ball Machine Method)", experiments were conducted on the modified graphene prepared in Example 3 and the unmodified graphene.
[0080] Select solvent oil that complies with GB1922-1980 "Solvent Oil" as the base grease.
[0081] Sample 1: 3% of the modified graphene prepared in Example 3 was added to the base fat and mixed evenly.
[0082] Sample 2: Add 3% of unmodified graphene into the base grease and mix well.
[0083] Test method: Under load, a steel ball on top rotates against three stationary steel balls on the surface of which the test grease (sample) is coated. After the test, the wear scar diameters of the three steel balls on the bottom are measured, and the anti-wear performance of the grease is judged by the average wear scar diameter.
[0084] Test conditions: test temperature: 75±2℃, spindle speed: 1200±50r / min, test load: 392±2N, test time: 60±1min.
[0085] Test results:
[0086] like Figure 1-3 As shown, the wear scar diameters of the three steel balls after treatment of Sample 1 are 0.611 mm for Ball No. 1, 0.613 mm for Ball No. 2, and 0.634 mm for Ball No. 3.
[0087] The raw material of sample 2 is unmodified graphene. The result of the four-ball experiment is that the four balls are stuck after running for 32 seconds and cannot rotate, which means that the unmodified graphene cannot play an anti-wear effect.
[0088] Based on the above situation, it can be seen that the modified graphene prepared in this application has good extreme pressure and wear resistance.
[0089] (ii) The modified graphene prepared in Example 3 and Example 6 was subjected to a thermal conductivity test according to GB / T5990-2021 “Test method for thermal conductivity, specific heat capacity and thermal diffusion coefficient of refractory materials”, and the thermal conductivity of the modified graphene prepared in the two examples was measured. The results are shown in Table 1.
[0090] Table 1
[0091] sample Test temperature Thermal conductivity W / (m·K) Example 3 25℃ 0.835 Example 6 25℃ 0.729
[0092] From Table 1, it can be seen that the thermal conductivity of the modified graphene prepared in the present application is very good, and the thermal conductivity of the modified graphene prepared in Example 3 is even better.
[0093] In summary, the present application adjusts the pH value of the ethanol solution with sodium hydroxide, then adds graphene powder to modify it, adjusts the pH value with acid after modification, then washes with water to remove residual sodium hydroxide, and finally dries and crushes it. The obtained modified graphene has excellent extreme pressure wear resistance, thermal conductivity and electrical conductivity.
[0094] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. A method for preparing modified graphene, characterized in that: The steps include: Take graphene, add it to an ethanol solution, add sodium hydroxide to adjust the pH value to 10, and obtain a mixed solution; The mixed solution is stirred for reaction, and then filtered to obtain a filter residue; Put the filter residue into a dilute acid solution and react until the pH value of the solution is 7, wash with water and drain, and then dry the filter residue; After the dried filter residue is crushed, pinene alcohol, nano copper oxide and the filter residue are evenly mixed in a weight ratio of 0.1:1:1, and treated at 450-490° C. for 2-4 hours in an ammonia atmosphere to obtain a modified graphene product.
2. A method for preparing modified graphene according to claim 1, characterized in that: The particle size of the graphene is 50-150nm.
3. A method for preparing modified graphene according to claim 1, characterized in that: The ratio of graphene to ethanol is 1 g:3 mL.
4. The method for preparing modified graphene according to claim 1, characterized in that: The ethanol concentration is 95%.
5. The method for preparing modified graphene according to claim 1, characterized in that: The mixed solution was stirred for reaction for 3-5 hours and then allowed to stand for 2 hours.
6. The method for preparing modified graphene according to claim 1, characterized in that: The dilute acid solution is specifically dilute sulfuric acid with a concentration of 7%.
7. The method for preparing modified graphene according to claim 1, characterized in that: The filter residue was washed with water and repeated 2-4 times.
8. The method for preparing modified graphene according to claim 1, characterized in that: The drying condition is to dry the filter residue at a temperature of 55-65° C. for 4-6 hours.
9. The method for preparing modified graphene according to claim 1, characterized in that: The crushing condition is to crush the filter residue at a rotation speed of 30000r / min for 40-90s.
Citation Information
Patent Citations
Modified graphene and preparation method thereof
CN102910623A
